Teaching Daily Conversational Language to Toddlers at PAUD Tunas Mekar in Melatiwangi Village, Bandung - S, Renda Sandi; Lianingsih, Nestia (Research Collaboration Community (Rescollacom), 2024)
Language is a tool of social interaction or communication because humans are basically social creatures. Humans have spoken since birth, although only in the form of vague or unclear sounds, but still in the form of signs or symbols that emit sounds, therefore it is called baby speech. Children first learn a language by speaking simple spellings until they can speak it well, which is called mother tongue or first language. In general, parents often do not have a good way of control in the process of fostering their children to be able to speak and speak, thus making children easily close themselves and have difficulty communicating with speakers. The purpose of this article is to find out early childhood language acquisition at the phonological, semantic, and syntactic levels through psycholinguistic research using qualitative methods using data collection techniques that underlie language acquisition: Several hypotheses, such as 1) conscience hypothesis, 2) tabularasa hypothesis, 3) cognitive universality hypothesis. Whether or not a child is good at language, raises the question of how important the role of parents is in child development, and how it can be controlled to minimize language problems faced by children